26.0k views
1 vote
0 = x^2 + 6x - 2 I need to know how to solve for this problem .

2 Answers

1 vote

Answer:

Explanation:

This equation should use this type of formula

a(x[ax^{2} +bx+c=0 with this formula


(-b+\sqrt{b^(2)-4(a)(c) }) /2a   \\(b+\sqrt{b^(2)-4(a)(c) }) /2a

in this case is imposible because doesn´t exist a negative square root so is indeterminate

User Abdelrahman
by
4.5k points
3 votes

Answer:

x = 2/7

Explanation:

0 = x^2 + 6x - 2

0 = x + 6x - 2

0 = 7x - 2

2 = 7x

2/7 = 7x/7

2/7 = x

User Franchelly
by
5.2k points